Improving students ability in counting multiple with Things around on math lesson of fourth grade Students in odd semester no.33 gurun panjang Kecamaatan koto xi tarusan - Amril Amril (Jurnal Ilmiah Pendidikan Scholastic, 2017)
Low mastery of the ability to calculate multiplication in pe, the lesson is due to less precisely the model of learning and media used. So students become inactive, easily bored, and less attention to teacher explanations. Therefore to improve the multiplication counting ability Required model of learning with appropriate media. One of them is the model of learning by using the media objects nearby. Based on the results of a daily test of mathematics lessons on multiplication multiplication shows that less successful learning. In the case according to the teacher's information in the daily learning has been explained orally, have been given examples, and even have been given the questions of practice and provide opportunities to students To ask, but they did not take advantage of the opportunity. This study aims to improve the ability to calculate multiplication fourth grade students of the first semester of S D Foreign N o. 33 Long Desert Sub Koto XI Tarusan. South Coastal District with total students 49 children, 25 children and 24 children Students daughter male student. The data in this study were obtained from interviews, questionnaires, observation results of action, and evaluation results. This study was conducted in two cycles. Each cycle is done based on the stages: Prepare an action plan, Implement action, Observation, and Analysis followed by reflection. The results showed that according to the results of observations of researchers on preaction is in students less active learning, easy tosaturate, and pay attention to students on teacher explanation is very small. In the first cycle-1 of the mastery of the material before the learning is given 31%, after the activity takes place students activeness shows: active students 58%, students are 30%, and 12% passive students. Student cooperation: active students 62%, students are 28%, and passive students 10%. While the result of average evaluation 68 with students complete 33 students and not complete 16 students.Hasi l-2 action in cycle action sebelun material penguasan 48%. After the action is done student activity: active students 78%, students are 18% and 4% passive students. Student cooperation: active students 84%, students are 14%, and 2% passive students. Evaluation result Average 76 students complete 46 complete students and 3 students not yet completed. Based on the above results kan It can be concluded that learning with the nearest media objects can improve the ability to calculate multiplication, increase student activity, and increase student cooperation in completing group tasks. Learning becomes enabling so students are not easily saturated